Potential biomarkers identified by tandem mass tags based quantitative proteomics for diagnosis and classification of Guillain–Barré syndrome. (30th December 2021) - Ding, Yaowei; Shi, Yijun; Wang, Lijuan; Li, Guoge; Osman, Rasha Alsamani; Sun, Jialu; Qian, Lingye; Zheng, Guanghui; Zhang, Guojun
Abstract: Background and purpose: Guillain–Barré syndrome (GBS) is an acute inflammatory autoimmune and demyelinating disease of the peripheral nervous system. Currently, valid biomarkers are unavailable for the diagnosis of GBS. Methods: A comparative proteomics analysis was performed on the cerebrospinal fluid (CSF) from 10 patients with GBS and 10 patients with noninflammatory neurological disease (NND) using the tandem mass tags technique. The differentially expressed proteins were analyzed by bioinformatics, and then the candidate proteins were validated by the enzyme‐linked immunosorbent assay method in another cohort containing 160 samples (paired CSF and plasma of 40 patients with GBS, CSF of 40 NND patients and plasma of 40 healthy individuals). Results: In all, 298 proteins were successfully identified in the CSF samples, of which 97 differentially expressed proteins were identified in the GBS and NND groups. Three key molecules were identified as candidate molecules for further validation. The CSF levels of TGOLN2 and NCAM1 decreased in GBS patients compared with NND patients, whereas the CSF levels of APOC3 increased. The enzyme‐linked immunosorbent assay results were consistent with our proteomics analysis. Interestingly, in the validation cohort, serum APOC3 levels in the GBS group were consistent with those in the CSF samples and significantly higher than those in the healthy control group. Conclusions: Our preliminary data suggest that the CSF protein expression profile of patients with GBS is different from that of patients with NND. Moreover, alterations of TGOLN2, NCAM1and APOC3 may be used as novel biomarkers for identifying patients with GBS. Abstract : Comparative proteomics analysis was performed on the cerebrospinal fluid (CSF) from 10 patients with Guillain–Barré syndrome (GBS) and 10 patients with noninflammatory neurological disease (NND) using the tandem mass tags technique. 298 proteins were successfully identified in the CSF samples, of which 97 differentially expressed proteins were identified in the GBS and NND groups. The CSF protein expression profile of patients with GBS is different from that of patients with NND.